2022
DOI: 10.1111/ina.13159
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the negative effects of raised bedroom temperature and reduced ventilation on the sleep quality of elderly subjects

Abstract: Aging populations are a world-wide concern. The Chinese demographic statistics announced in March 2021 showed that the percentage of the population 60 years old or more in China was 18.7% (260 million). People experience many physiological and psychological changes in old age, including a decrease in sleep quality and quantity and altered sleep structure. 1 Sleep disturbance of about 50% has been observed among the elderly in many countries. [2][3][4][5][6][7] Sleep disturbance is detrimental to both the physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Three studies, summarized in Table 1, met criteria for inclusion in the analysis. Two studies were controlled trials, 23,24 while one was an observational cohort study. 25 Huang et al recruited participants (n = 41) into one of three intervention groups or a control group to assess the effect of these interventions (subsidies for air conditioning, education about health and environmental heat, and use of sprinklers to cool home exteriors) on sleep quality and CV measurements during a heatwave.…”
Section: Summary Of Articlesmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies, summarized in Table 1, met criteria for inclusion in the analysis. Two studies were controlled trials, 23,24 while one was an observational cohort study. 25 Huang et al recruited participants (n = 41) into one of three intervention groups or a control group to assess the effect of these interventions (subsidies for air conditioning, education about health and environmental heat, and use of sprinklers to cool home exteriors) on sleep quality and CV measurements during a heatwave.…”
Section: Summary Of Articlesmentioning
confidence: 99%
“…23 Yan et al performed a controlled, cross-over trial, placing participants (n = 16) in one of four room permutations, with rooms either 27ºC or 30ºC and either employing mechanical ventilation systems to circulate ltered outdoor air or not. 24 Kim et al observed the effects of a heat wave on elderly residents of rural communities in South Korea (n = 104). 25…”
Section: Summary Of Articlesmentioning
confidence: 99%
See 3 more Smart Citations